Pola Pendidikan Karakter Kristiani Era New Normal Pada Generasi Alfa - Jeane M. Tulung; Irene Preisilia Ilat; Yunita Kemur; Michael Fabio Polii (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2022)
The study aims to identify, analyze and describe how the normal new era Christian character education pattern of the alpha generation at GMIM buloh elementary school, along with inhibitory factors and efforts to overcome inhibitory factors. The weakening of Christian character in the normal new era alpha generation reflected in the GMIM Buloh elementary school has been one of the reasons researchers elevate the heading "a normal new era Christian character education pattern for the alpha generation at GMIM Buloh elementary." The methods used in this study are descriptive qualitative methods using data collection techniques by observation, interview, and documentation. Research indicates that the pattern of Christian character education used particularly in the new normal era of the alpha generation at GMIM Buloh elementary school is through: (1) guiding, mentoring, regulation, motivation, example, and using the appropriate spiritual and wise quotations in school wards. (2) the barriers school and teacher face are limited learning times, teachers and students struggle with using online learning media, lack of support from parents, excessive gadget use, poor social environment, and also internal factors that come from within the student body. (3) as for the effort the teacher makes with the parents, teaching them repeatedly and setting a good example in life.